The Application of K-Nearest Neighbours Algorithms for the Classification of Fashion Trend - Saputro, Nugroho Dwi; Wibowo, Setyoningsih; Darmaputra, Mochamad Fadjar (Prodi Sistem Informasi FST Universitas Jambi, 2019)
The commerce department in indonesia has been formulating indonesia economic development plan creative explain about the evolution of the year 2025 creative economy, The shift from agriculture to the industrial era and the era of information and now entering the era of economic globalization. The development of industries create a pattern of work the production and distribution of cheap and more efficient. Fashion industry is one of the creative economy development Creative economy in many countries today encourage the people. Fashion or mode of itself is the activity associated with the design, the production of, consultation and the distribution of the product of fashion .Producers fashion industry composed of fashion clothing and accessories, fashion industry bag manufacturers, shoes and accessories. In clothes creation, the trend of being important aspect .Designers indonesia today still follow the trend of europe are affected by the type of the season. Decision-making on the basis of the data and accurate information will result in a decision to fashion trend clasification on creative industries can be done by adopting the approach of data mining. According to Tan Pang-Ning data mining is a process that done automatically to find information that is useful in a repository big data.